Profil Pemahaman Kesuksesan Karir Siswa Dalam Melanjutkan Pendidikan Ke Perguruan Tinggi (Study Kasus Di Kelas XII SMA Negeri 3 Cirebon) - Saputri, Dina Indah; Kiswanto, Andi; Hendriady, Deddy (Jurnal Eksplorasi Bimbingan dan Konseling, 2024)
This research is a qualitative research. The subjects of the research were students and BK teachers at SMA Negeri 3 Cirebon. From the population of grade XII students of SMA Negeri 3 Cirebon, there were 320 students and the sample used with a 10% chi square error rate from the population of 147 students. Data collection was carried out by conducting observations, interviews, and documentation. Data analysis was carried out on the forms of career guidance implementation carried out in schools. Through career guidance activities, students are equipped with activities related to how to plan for the future, meaning that students are given direction and knowledge about the world of work according to their desired field from the beginning of their entry. That way, students plan their careers accordingly without any mistakes and students can succeed in achieving their desired careers.